Common themes between Ibn Farid and Hafez - محسن راثی (تاریخ ادبیات)
Hafez is the greatest mystical lyricist of Iran and one of the geniuses of the human world, and Ibn Farid Sharaf al-Din Omar, who died in 632 AH, is the greatest speaker of Sufism in the Arabic language. There are many differences between Hafez and Ibn Farid in terms of mysticism and theoretical wisdom, and there are many commonalities in terms of many mystical meanings and themes. This article tries to show some of the similarities and comparisons between these two great personalities, one from the west of Islamic countries and the other from the east of Islamic countries, and they lived one hundred and sixty years apart, using and quoting the poetic evidences of both geniuses and lovers of God, which is important and valid from the point of view of the history of literature and comparative literature.